Hybrid Structure of the Type 1 Pilus of Uropathogenic Escherichia coli. Issue 40 (12th August 2015) - Habenstein, Birgit; Loquet, Antoine; Hwang, Songhwan; Giller, Karin; Vasa, Suresh Kumar; Becker, Stefan; Habeck, Michael; Lange, Adam
Abstract Type 1 pili are filamentous protein assemblies on the surface of Gram‐negative bacteria that mediate adhesion to host cells during the infection process. The molecular structure of type 1 pili remains elusive on the atomic scale owing to their insolubility and noncrystallinity. Herein we describe an approach for hybrid‐structure determination that is based on data from solution‐state NMR spectroscopy on the soluble subunit and solid‐state NMR spectroscopy and STEM data on the assembled pilus. Our approach is based on iterative modeling driven by structural information extracted from different sources and provides a general tool to access pseudo atomic structures of protein assemblies with complex subunit folds. By using this methodology, we determined the local conformation of the FimA pilus subunit in the context of the assembled type 1 pilus, determined the exact helical pilus architecture, and elucidated the intermolecular interfaces contributing to pilus assembly and stability with atomic detail.